Declamation, paternity, and Roman identity : authority and the rhetorical self - Gunderson, Erik (Cambridge University Press, 2003)
For centuries declamation was a staple of education and cultured literary life in the Roman world. This book radically re-evaluates the genre, its social import, and its place in the history of the Western self. It will interest specialists in classics, rhetoric, queer studies, and psychoanalytic literary criticism.